2001
DOI: 10.1038/sj.onc.1204884
|View full text |Cite
|
Sign up to set email alerts
|

Signal-specific and phosphorylation-dependent RelB degradation: a potential mechanism of NF-κB control

Abstract: RelB is an unusual member of the Rel/NF-kB family of transcription factors which are involved in oncogenic processes. Due to a relaxed control by the IkBs, the cytosolic NF-kB inhibitors, RelB is constitutively expressed in the nuclei of lymphoid cells. We show here that RelB is inducibly degraded upon activation of T cells in a fashion similar to the IkBs. However, RelB degradation di ers from that of IkBs since it is not induced by TNFa but only by T cell receptor or TPA/ ionomycin stimulation. Moreover, Rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
69
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 22 publications
4
69
0
Order By: Relevance
“…The stimulus-induced RelB degradation is an alternative IkB-independent mechanism of NF-kB regulation known to occur not only in T cells but also in other lymphoid and non-lymphoid cells (Marienfeld et al, 2001(Marienfeld et al, , 2003. RelB is one of the five mammalian Rel proteins of which the NF-kB dimer is composed.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The stimulus-induced RelB degradation is an alternative IkB-independent mechanism of NF-kB regulation known to occur not only in T cells but also in other lymphoid and non-lymphoid cells (Marienfeld et al, 2001(Marienfeld et al, , 2003. RelB is one of the five mammalian Rel proteins of which the NF-kB dimer is composed.…”
mentioning
confidence: 99%
“…Both processes differ in their kinetics with RelB degradation being delayed compared with IkB degradation. Further, RelB degradation is signal specific and cannot be induced by tumour necrosis factor-a, a potent activator of NF-kB (Marienfeld et al, 2001).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the physiological significance of RelB-phosphorylation has been elusive especially because a previous study based on analysis of T-cells reported that similar to the IkB molecules, the consequence of RelB-S573 phosphorylation is its degradation suggesting an inhibitory role for RelB 44,55 . On the contrary our results presented here indicate that phospho-RelB-S573 in MM In MM cells RelB and ERK1 constitutively interact with each other.…”
Section: Discussionmentioning
confidence: 99%